Legal Protection Of Communities Who Have Customary Land Rights (Case Study of Decision Number 2087 K/Pdt/2012) - Kholis, Fikri Al (TABELLIUS: Journal of Law, 2024)
This study examines legal protection for communities with rights to customary land through a case study of Decision Number 2087 K/Pdt/2012.Customary land disputes are complex issues and often cause prolonged conflict in Indonesia. This study aims to evaluate the extent to which court decisions in the case reflect fair legal protection for indigenous peoples and their implications for the recognition of customary land rights in Indonesia. This type of research is normative legal research using a normative legal approach method. The method of collecting data for this study is a literature study that will be analyzed qualitatively by examining court decision documents, relevant laws and regulations, and related literature. The results of this study examine how Indonesian law views the legal protection of customary land rights communities and reveals how the results of the settlement of customary land disputes in Decision Number 2087 K / Pdt / 2012 are fair in accordance with applicable regulations, the legal system to ensure that the rights of indigenous peoples are recognized and protected fairly. In addition, this study uses the theory of legal protection and the theory of legal justice as analytical tools in rejecting data that aims to continue to contribute to efforts to improve legal protection for indigenous peoples and ensure the application of the principle of justice in the national legal system.